Comparative Analysis of Sharia and Conventional Peer-to-Peer Lending for MSMEs - Mutmainah Mutmainah; Tri Hidayati (Academica: Journal of Multidisciplinary Studies, 2025)
Objective: This study aims to comparatively analyze the differences in risks, costs, and social impacts between Sharia and conventional Peer-to-Peer (P2P) lending on Micro, Small, and Medium Enterprises (MSMEs). Method: The research adopts a library research approach by utilizing secondary data obtained from the Financial Services Authority (OJK), academic literature, and various scholarly journals related to fintech and Islamic finance. Result: The findings indicate that conventional P2P lending operates under a fixed interest-based system, in which credit risk is fully borne by the borrower, whereas Sharia P2P lending applies profit-and-loss sharing and risk-sharing principles through contracts such as mudharabah, musyarakah, or wakalah bil ujrah. The cost structure in the Sharia system is more flexible as it does not involve elements of riba, while the conventional system imposes fixed interest rates that may place a financial burden on MSMEs. From a social perspective, P2P lending plays a significant role in expanding access to financing for MSMEs that are not yet served by formal financial institutions. Conclusion: The Sharia model is considered more equitable as it emphasizes partnership, transparency, and economic justice in accordance with Islamic values. Therefore, Sharia P2P lending functions not only as an alternative financing mechanism but also as an instrument for sustainable and socially just economic empowerment.